Comparison of In Vitro Antibacterial Activities of Gentamicin and Verdamicin - Yu, Pauline K. W. (1974)
The in vitro activities of verdamicin and gentamicin were studied in parallel against 1,049 bacterial isolates. Verdamicin demonstrated activity similar to that of gentamicin against members of the family Enterobacteriaceae and against Pseudomonas aeruginosa at 2 and 8 μg/ml, respectively. Proteus rettgeri and Providencia stuartii were notably more susceptible to verdamicin. The new aminoglycoside was also highly active against staphylococci but was not effective against group D streptococci.